Beta-cyclodextrin-zinc acetylacetonate (β-CD@ZnA) inclusion complex formation as a sustainable/smart nanocarrier of corrosion inhibitors for a water-based siliconized composite film: Integrated experimental analysis and fundamental computational electronic/atomic-scale simulation. (15th September 2020) - Dehghani, Ali; Bahlakeh, Ghasem; Ramezanzadeh, Bahram
Abstract: Corrosion inhibitors encapsulation in various nano-carriers is one of the best strategies for the construction of composite polymeric coatings with promising self-healing potency against harsh corrosive environments. In the present study, for the first time, a novel corrosion inhibitor nano-carrier was constructed by encapsulating the complex organic-inorganic inhibitors based on zinc acetylacetonate (ZnA) inside beta-cyclodextrin (β -CD). The smart anti-corrosion potency of the designed inclusion complex system was thoroughly explored in detail, applying complementary experimental (electrochemical and morphological) and electronic/atomic-scale computational investigations. The synthesized particles were examined by Fourier transform infrared spectroscopy (FT-IR), Raman spectroscopy, X-ray diffraction (XRD) analysis, and ultraviolet spectroscopy (UV–Vis). The thermal stability of the constructed nano-carriers was studied by the thermogravimetric analysis (TGA) technique, and the β -CD-ZnA sample showed about 11% remained weight (at 550 °C) higher than the unloaded β -CD, indicating the successful ZnA encapsulation in the interior cavity of the β -CD particles. The electrochemical measurement outcomes revealed that the β -CD-ZnA inclusion complex could inhibit metal corrosion with mixed anodic/cathodic protection mechanisms. The field emission scanning electron microscope (FE-SEM) micrographs proved the significant corrosion inhibition potency of the β -CD-ZnA inclusion complex toward the steel corrosion in NaCl solution. The electrochemical impedance spectroscopy (EIS) Results ensured that the incorporation of the β-CD-ZnA particles into a hybrid silane matrix caused significant coating corrosion resistance improvement (about 30 kΩ cm 2 ). The atomic-scale Monte Carlo connected with molecular dynamics simulations, supported the adsorption of β -CD-ZnA inclusion over the metallic adsorbent. Graphical abstract: Image 1 Highlights: A novel high-performance nano-carrier based on zinc acetylacetonate reinforced beta-cyclodextrin was developed. The EIS evaluations ensured significant silane matrix corrosion resistance improvement in the presence of β -CD-ZnA. Monte Carlo and molecular dynamics simulations supported the adsorption of β -CD-ZnA over the metallic adsorbent.